Bioactive Glass Reinforced Polyurethane Scaffolds- Effect Of Pu Solution Concentration - Rozani, Mohd Afifi (Universiti Sains Malaysia, 2017)
In this research, porous bioactive glass (BG) reinforced polyurethane (PU) composite scaffolds with different PU mass was fabricated by using salt leaching technique. There are a number of characterization techniques applicable for determining the chemical and physical properties of the fabricated porous scaffolds. SEM analysis is performed to observe the microstructure at the cross-sectional area of porous scaffolds. The porous scaffolds prepared exhibit the closed pore as concentration of PU increase. The porosity showed the increasing trend as increasing the PU solution concentration from 8. wt% to 12. wt%. For the result of compressive strength, it also showed an increasing trend in compressive strength as increasing in PU concentration. 12. wt % has the highest value of compressive strength which is (0.13 Mpa) compare to the lowest one which is 0.04 Mpa. The result also showed that the composite scaffolds prepared with more PU concentration (0.28 Mpa) has higher compressive modulus than the scaffolds with lower amount of PU (0.12 Mpa.